Un reconocimiento ambivalente: Políticas de escrituración en barrios populares del Gran Buenos Aires - Nuñez, Javier (2025)
This article systematizes a series of qualitative surveys carried out in five popular neighborhoods in the south of Greater Buenos Aires in relation to the development of land titling policies. It is argued that the partial results of these programs refer to a type of State presence that shifts the boundaries between the formal and the informal, favoring the circulation of land certifications other than deeds. In addition, differences in the implementation of deeds were considered in terms of the type of their position in municipal popular politics, the moment of occupation and the type of popular neighborhood, as well as the housing trajectories of their inhabitants. As a result, regularization policies tend to generate normatively ambivalent recognitions, which legally enshrine possession but do not equate to deeds.